2016
DOI: 10.24218/msear.2015.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Hemostatic Agents Using Thrombelastography

Abstract: Hemorrhage is one of the leading causes of death in civilian and military trauma. Thrombelastography (TEG) quantitatively measures the viscoelastic changes of whole blood during clotting, from the beginning of coagulation to the end with fibrinolysis. In this study, we successfully developedand used a TEG method to compare a well-known Chinese herb medicine (i.e., Yunnan Baiyao) for hemorrhage control with other commercial hemostatic products (e.g., Celox TM and QuikClot TM ) and chitosan in the form of dry po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Thromboelastographic studies. The studies were performed as per earlier reported protocol to understand the hemostasis process and where the material impacts the coagulation cascade [25,26]. Measurement of Tr-AuNPs and native tranexamic acid was carried out at an equivalent concentration of 9 μg ml −1 , using whole blood as a control.…”
Section: Thrombus Weight: (Final Weight Of the Sample Vial-initial We...mentioning
confidence: 99%
“…Thromboelastographic studies. The studies were performed as per earlier reported protocol to understand the hemostasis process and where the material impacts the coagulation cascade [25,26]. Measurement of Tr-AuNPs and native tranexamic acid was carried out at an equivalent concentration of 9 μg ml −1 , using whole blood as a control.…”
Section: Thrombus Weight: (Final Weight Of the Sample Vial-initial We...mentioning
confidence: 99%
“…To understand the hemostasis process and where the material impacts, TEG studies were performed as per an earlier reported protocol. [38][39][40][41][42] Measurement of Ca-MOF concentrations ranged from 50 mg ml À1 to 1000 mg ml À1 using whole blood as control was performed. Specific to this study, blood samples were obtained from healthy volunteers after obtaining consent as per the institutional ethical committee guidelines (ECR/824/Inst/DL/2016/RR-19) through venipuncture and collected into separate vacutainers with 3.2% sodium citrate solution and gently inverted three times.…”
Section: Materials Advances Papermentioning
confidence: 99%